Artists' magazines : an alternative space for art - Allen, Gwen (Cambridge, Mass. : MIT Press, 2011)
During the 1960s and 1970s, magazines became an important new site of artistic practice, functioning as an alternative exhibition space for the dematerialized practices of conceptual art. Allen looks at the most important of these magazines in their heyday and compiles an illustrated directory of hundreds of others.
This is not to be looked at : Artforum in the 1960s and 1970s -- The magazine as a medium : Aspen, 1965-1971 -- Art on and off the page : 0 to 9, 1967-69 -- An artists' magazine : Avalanche, 1970-76 -- The magazine as an alternative space : Art-rite, 1973-1978 -- The magazine as mirror : File, 1972-1989 -- Real life, 1979-1994 -- Epilogue : International activity : Interfunktionen, 1968-1975.
boek